FRI0118 RISK OF LIVER FIBROSIS ON TRANSIENT ELASTOGRAPHY IN PATIENTS WITH RHEUMATIC DISEASE UNDER LONG-TERM METHOTREXATE TREATMENT. (2nd June 2020) - Choi, S. J.; Lee, J. S.; Nam, S. H.; Seo, W. J.; Oh, J. S.; Hong, S.; Kim, Y. G.; Lee, C. K.; Yoo, B.
Abstract : Background: Methotrexate (MTX) is a cornerstone drug for the treatment of rheumatic disease and low doses of MTX are both tolerable and safe, with monitored toxicity, assessed via the liver function test. However, there is still controversy regarding the risk of liver fibrosis with long-term use of MTX. Transient elastography is commonly used to assess and monitor fibrosis progression in patients with chronic liver disease. Objectives: The present study aims to investigate liver fibrosis using transient elastography and related factors in patients with rheumatic disease receiving long-term MTX. Methods: The present retrospective, longitudinal, cross-sectional study included patients with an autoimmune disease who are taking cumulative MTX dosed over 7 g, and who had liver fibrosis upon examination using transient elastography. Liver fibrosis was defined as liver stiffness, valued over 7.2 kPa. Logistic regression analysis was performed to identify factors associated with liver fibrosis, and receiver operating characteristics analysis was used to determine the predictive value of each factor. Results: We included 83 patients with autoimmune disease, with a median MTX cumulative dose of 11.6 (range 7.3-16.0) g. Sixty-eight patients (81.9%) had rheumatoid arthritis (RA), and 13 patients (15.7%) had Takayasu arteritis. The median MTX exposure duration was 18 (range 9-31) years. The median liver stiffness value was 4 (range 1.8-10.2) kPa. Five patients (6%) showed liver fibrosis (3 patients; RA, 2 patients; Takayasu arteritis). In the linear regression analysis, cumulative MTX dose showed a tendency towards a positive correlation with increasing liver stiffness value (r2 =0.039, p = 0.074). In the logistic regression analysis, cumulative MTX dose was associated with a higher risk of liver fibrosis (OR: 1.734, 95% CI: 1.060–2.837, p = 0.029). In addition, cumulative MTX dose had an area under the curve (AUC) of 0.813 (95% CI 0.695-0.930) and a sensitivity of 80% and specificity of 71.8% at a cut-off value of 12.7 g. Conclusion: Liver fibrosis was observed in 6% of patients with long-term MTX use and higher cumulative MTX doses increased the risk of liver fibrosis. Thus, transient elastography should be considered in patients exposed to high cumulative doses of MTX. Disclosure of Interests: None declared